Average Error: 0.0 → 0.0
Time: 1.4s
Precision: 64
$\left(a + b\right) + \left(c + d\right)$
$\left(c + d\right) + \left(a + b\right)$
\left(a + b\right) + \left(c + d\right)
\left(c + d\right) + \left(a + b\right)
double f(double a, double b, double c, double d) {
double r41375050 = a;
double r41375051 = b;
double r41375052 = r41375050 + r41375051;
double r41375053 = c;
double r41375054 = d;
double r41375055 = r41375053 + r41375054;
double r41375056 = r41375052 + r41375055;
return r41375056;
}


double f(double a, double b, double c, double d) {
double r41375057 = c;
double r41375058 = d;
double r41375059 = r41375057 + r41375058;
double r41375060 = a;
double r41375061 = b;
double r41375062 = r41375060 + r41375061;
double r41375063 = r41375059 + r41375062;
return r41375063;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\left(a + b\right) + \left(c + d\right)$
2. Final simplification0.0

$\leadsto \left(c + d\right) + \left(a + b\right)$

# Reproduce

herbie shell --seed 1
(FPCore (a b c d)
:name "(a+b)+(c+d)"
(+ (+ a b) (+ c d)))